Iowa RBA, October 26, 1998 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1998)
Iowa RBA for October 26, 1998. Highlights include Ruff and Smith's Longspur. Includes notes for updates for October 28, October 29, and October 31. Epson - sheet feed/flatbed